THE PROBLEMS OF DEMOCRACY: A CRITICAL STUDY OF ARUNDHATI ROY’S SELECT ESSAYS (International Journal of Food and Nutritional Sciences, 2022)
Arundhati Roy is an active critic of pseudo-development. She is not against development but against the way ‘development’ is carried out. The majority of the benefits go to the capitalists. She does not deny that fact that a nation needs ‘progress’ and ‘development’ but people in India especially the marginalized are suppressed in the name of progress and development. When these marginalized raise their voice, they are tagged as anti-national. Her essays unfold what is happening in the democratic India, about their consequences and aftermath. She also assumes what happens if the democracy is used wrongly. Her essays not only provide an overview but also a detailed under view of events that is happening in India.